2018
DOI: 10.1002/mbo3.604
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of coral‐associated microbiomes during a thermal bleaching event

Abstract: Coral‐associated microorganisms play an important role in their host fitness and survival. A number of studies have demonstrated connections between thermal tolerance in corals and the type/relative abundance of Symbiodinium they harbor. More recently, the shifts in coral‐associated bacterial profiles were also shown to be linked to the patterns of coral heat tolerance. Here, we investigated the dynamics of Porites lutea‐associated bacterial and algal communities throughout a natural bleaching event, using ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 81 publications
(134 reference statements)
9
26
1
Order By: Relevance
“…These groups were closely related to pathogens of other terrestrial and as well as marine organisms (Ayulo et al, 1994;Wang et al, 2009;Boss et al, 2016), which indicates the role of opportunistic exogenous pathogens. Besides, an increase of Caulobacter abundance (8.09%) has also been associated with SGA coral which is comparable to the study of Pootakham et al (2018) where they reported the predominance of Caulobacterales during bleaching of Porites lutea. In addition, A high abundance of Candidatus Solibacter and Candidatus Koribacter were observed in healthy samples (4.2 and 2.2% respectively) when compared to diseased ones (<0.01%).…”
Section: Resultssupporting
confidence: 84%
“…These groups were closely related to pathogens of other terrestrial and as well as marine organisms (Ayulo et al, 1994;Wang et al, 2009;Boss et al, 2016), which indicates the role of opportunistic exogenous pathogens. Besides, an increase of Caulobacter abundance (8.09%) has also been associated with SGA coral which is comparable to the study of Pootakham et al (2018) where they reported the predominance of Caulobacterales during bleaching of Porites lutea. In addition, A high abundance of Candidatus Solibacter and Candidatus Koribacter were observed in healthy samples (4.2 and 2.2% respectively) when compared to diseased ones (<0.01%).…”
Section: Resultssupporting
confidence: 84%
“…Bacteria from the genus Oceanospirillum are frequently observed in healthy coral colonies [48,49], while members of the phylum Lentisphaerae are common in the fish gut [50] and healthy corals [48]. Sequences from the order Rhodospirillales are commonly found in high abundance in stressed and diseased coral colonies [9,[51][52][53], indicating an opportunistic character. Given that our experiment lasted for 48 h, the persistence of potential beneficial symbionts and opportunistic bacterial taxa and their consequences on coral microbiomes and health will have to be further investigated over longer time period.…”
Section: Discussionmentioning
confidence: 99%
“…However, microbial communities can be disrupted by changes in ocean conditions, such as warming water temperatures, and thus lead to decline in host health (Thurber et al, 2009;Blanquer et al, 2016). Many sponge and coral diseases and mortality events have been linked to anomalously high water temperatures; new research provides evidence that the warm conditions do not harm the organism directly, but alter their microbial composition, leading to a decline in host health and increased vulnerability to pathogens (Thurber et al, 2009;Pootakham et al, 2018). Sponge microbiomes may even be used as a proxy for sponge health, as microbiome changes can be observed in the sponge tissue before a disease is visually evident (Blanquer et al, 2016).…”
Section: Microbiome Function In Sponges and Coralsmentioning
confidence: 99%